Prototype Sistem Monitoring Infus Berbasis IoT (Internet Of Things ) - Akbar, Taufik; Gunawan, Indra (Universitas Hamzanwadi, 2020)
The development of increasingly sophisticated medical science and technology has an impact on the development of science and technology in the field of medical-devices. One of the existing equipment and is often used in hospitals, one of which is an IV. Currently in the world of health, infusion is still controlled manually. Because it takes time if the nurse has to go back and forth throughout the patient room. Not only is it time consuming, but there will be risks if it is too late to treat a patient whose infusion has run out. Technology needs to be used to minimize risks in the medical world, one of which is the application of IoT technology. This study aims to make it easier for nurses to control infusion conditions in real time using the concept of IoT ( the Internet of Things). The method used is the Waterfall method. This research uses hardware consisting of Load Cell with the HX711 module as a weight sensor, NodeMCU V3 as a processor, and Thingspeak Web server as the interface with the user. The results of the measurement of the tool made have an error of 0.25 Gram, sending data to the Thingspeak.com Server requires a good connection for maximum results.